EVALUASI PENERAPAN TAX PLANNING DALAM UPAYA MEMINIMALKAN PAJAK TERUTANG PADA CV XYZ - Anisa Frieda; Dwi Suhartini (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to study and evaluate how Tax Planning influences the reduction of the nominal amount of taxes payable. The research method uses a qualitative approach. The data collection techniques include observation and documentation by reviewing the company's financial statements. The researcher then processes all the collected data after data collection. The data analysis used in this research is qualitative descriptive data analysis, which is processed and described in the form of tables and narratives. The analysis results show that CV XYZ has taken appropriate steps in implementing tax planning to minimize the payable taxes. The company could save on tax payments through tax planning. CV XYZ paid corporate income tax amounting to Rp 117.142.064 before tax planning; after tax planning, the amount paid decreased to Rp 115.010.814, resulting in an efficiency of Rp 2.131.250.